Metal or nonmetal cooperation with a phenyl group: route to catalysis? a computational investigation - Ghatak, Kamalika; Mane, Manoj; Vanka, Kumar (ACS Catalysis, 2013)
Full quantum mechanical calculations demonstrate that cooperativity in the form of the activation of the M-C bond (M: transition metal or boron, C: the ipso carbon of the coordinated phenyl group) can lead to effective catalysis pathways. Calculations show that the presence of an aromatic bidentate ligand attached to a transition metal, or even a main group element, such as boron, can lead to effective catalysts for,a, range of important reactions, such as the dehydrogenation of ammonia borane and formic acid and the activation of the N-H, bond in aromatic amities. Moreover, it is shown that the design of tridentate pincer complexes with the aromatic group at a terminal end can lead to effective M-C cooperativity. As such, the current work introduces a new concept in cooperativity and bond activation chemistry.
Keywords: catalysis; Density functional theory; metal-ligand cooperativity; small molecule activation